2014
DOI: 10.1590/s1980-65742014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Improved exercise capacity in the heat followed by coconut water consumption

Abstract: Abstract-The aim of the present study was to assess the effects of prior ingestion of coconut water on fluid retention and exercise capacity in the heat as well as signs of gastrointestinal distress. Eight physically active men were recruited (age 23 ± 3 years, height 176 ± 6 cm, body mass 78 ± 7 kg) and performed three exercise capacity trials on a cycle ergometer in the heat (34 ± 1°C) after the ingestion of one of the following drinks: a) plain water (PW), b) flavored drink (FD), and c) coconut water (CW). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…The design implemented did not necessarily allow the past authors to investigate the effect of CW upon performance as the nature of the exercise may not be expected to change markedly (more exercise capacity than performance), and the participants did not consume any CW in the preceding 2-hour prior to the exercise test, hence the novelty of the current study. Laitano et al (2014) did however observe improvement in exercise capacity following the consumption of CW compared with PW when exercising in the heat (34°C, ~55% relative humidity). It may be the case that CW has more potential benefit under heat stress, but the results of the current study combined with those from Kalman et al (2012) suggest that CW has no apparent ergogenic benefit when consumed either during or post exercise in normothermic conditions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The design implemented did not necessarily allow the past authors to investigate the effect of CW upon performance as the nature of the exercise may not be expected to change markedly (more exercise capacity than performance), and the participants did not consume any CW in the preceding 2-hour prior to the exercise test, hence the novelty of the current study. Laitano et al (2014) did however observe improvement in exercise capacity following the consumption of CW compared with PW when exercising in the heat (34°C, ~55% relative humidity). It may be the case that CW has more potential benefit under heat stress, but the results of the current study combined with those from Kalman et al (2012) suggest that CW has no apparent ergogenic benefit when consumed either during or post exercise in normothermic conditions.…”
Section: Discussionmentioning
confidence: 73%
“…It was reported that CW was more effective than PW for subsequent exercise in hot conditions. Of note is that neither of the tests employed by Kalman et al (2012) nor Laitano et al (2014) measured performance per se, but rather exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Pemberian air kelapa sebelum dan juga selama latihan dilakukan oleh Laitano dkk. 11 Subjek penelitian diberi air biasa, minuman beresens jeruk, atau air kelapa 1 jam sebelum latihan bersepeda sampai terjadi kelelahan. Pemberian minuman sebanyak 10 mL/kgBB dilanjutkan selama latihan setiap 10 menit.…”
Section: Pembahasanunclassified
“…[1] Argue that when the body lacks fluids, the body will experience dehydration. Very strenuous aerobic physical activity will affect the increase in pulse rate and the need for efforts to overcome this recovery [2].…”
Section: Introductionmentioning
confidence: 99%